Evidence and experiment: Curating contexts of Anthropocene geology. (April 2023) - Rosol, Christoph; Schäfer, Georg N; Turner, Simon D; Waters, Colin N; Head, Martin J; Zalasiewicz, Jan; Rossée, Carlina; Renn, Jürgen; Klingan, Katrin; Scherer, Bernd M
Together with research teams from around the world, the Anthropocene Working Group (AWG) has been meticulously quantifying and scrutinizing the global stratigraphic imprint of human activities, the results of which are gathered in this thematic collection of papers in The Anthropocene Review . How can such empirical research, which so impressively articulates the end of a relatively stable Earth System in the mid-20th century, inform our ways of understanding and responding to the planetary crisis that the geological samples quietly represent? In this afterword to the collection we report and reflect on the joint undertaking of the AWG, Haus der Kulturen der Welt and the Max Planck Institute for the History of Science to bring geoscientific evidence, cultural experimentation and historical contextualization together in a shared public framework.